Linkage Stock Price, Trading Volume Activity, Stock Returns and Trading Frequency on Bid Ask Spread - Alkusani, Alkusani; Handayani, Anita; Rahmadani, Yosi Firda (INNOVATION RESEARCH JOURNAL, 2020)
The purpose of this study was to to examine the effect of stock prices, trading volume activities, stock returns and trading frequency of the bid ask spread of LQ45 company. Determination of the study sample consist of 42 companies conducted using purposive sampling method. As for hypothesis testing and research instruments using multiple linear regression analysis SPSS 20.0. Result of this study prove that all of the independent variable does not affect the bid ask spread